Analysis of the Current Challenges for Deep Underground Mines: Labour Productivity Improvement - Greberg, Jenny; Salama, Abubakary (Tanzania Journal of Engineering and Technology, 2020)
With much of the ore deposits close to the surface already discovered and mined, the mines are becoming deeper, and this brings multiple challenges. One of the challenges is the longer haul distance from active mining areas to the mine surface, hence longer transportation time of material and operators. Longer transportation time of operators may lead to the reduction of the labour productivity. Labour productivity in today ' s mines is a key importance, and is currently dependent on together with other factors that operators should be at the vehicles or working area on time. There has been some development in mine automation, but the vast majority of underground mine operations are still in need of operators. Several methods are available and can be used to transport operators to the underground working areas. These methods include mine vehicles, mine taxis, mine buses, monorail, and shaft system. As mine depth increases, the method with higher labour productivity will be of much useful in operator ' s transportation. The aim of this study is to investigate personal transportation methods for deeper underground operations by comparing labour productivity when using mine vehicle, mine taxi, mine buses, and monorail system. The results show that mine vehicle has higher labour productivity of up to 76% of available time, while mine buses have low labour productivity. It has been reveal that for shallow depth mines, a good option to improve labour productivity is to have few operators transported per cycle, while for deep mines, a transport system that is faster, accommodate few operators per cycle, less possibility to meet traffic will be the better option for labour productivity improvement. Keywords: Haul distance, Labour productivity, transportation method